Associations between dietary profiles and perfluoroalkyl acids in Inuit youth and adults - Aker, Amira; Ayotte, Pierre; Caron-Beaudoin, Élyse; De Silva, Amila; Ricard, Sylvie; Lemire, Mélanie (Science of The Total Environment, 2022)
Background: Perfluoroalkyl acids (PFAAs), a subset of perfluoroalkyl substances (PFAS), are synthetic chemicals used in industrial and consumer applications. They are exceptionally stable and highly mobile in the environment, and were detected in high concentrations in Arctic wildlife and Nunavik Inuit. The study's objective was to study the association between dietary profiles in Nunavik and plasma PFAAs concentrations. Methods: The study used data from the Qanuilirpitaa? 2017 Nunavik Inuit Health Survey (Q2017) (N = 1172) on Inuit adults aged 16-80 years. Nine PFAAs congeners were measured in plasma samples (six were detected). Dietary profiles were identified using latent profile analysis. Two sets of dietary profiles were included; the first included market (store-bought) and country foods (harvested/hunted from the land), and the second included only country foods. Multiple linear regression models regressed log-transformed PFAAs concentrations against the dietary profiles, adjusting for sociodemographic variables. Results: We identified statistically significant 24.54-57.55 % increases in all PFAAs congeners (PFOA, PFNA, PFDA, PFUnDA, PFHxS, and PFOS) in the dietary profile defined by frequent country food consumption compared to the dietary profile defined by frequent market food consumption. Individuals defined by low consumption of foods (related to food insecurity) had higher concentrations of six PFAAs compared to individuals with frequent market food consumption. The associations were stronger with profiles defined by more frequent country food consumption, and particularly those with increased marine mammal consumption. PFDA, PFUnDA, and PFOS were particularly associated with high country food consumption frequency, such that their concentrations increased by approximately 67-83 % compared to those reporting no or very little consumption of any country foods. Conclusions: Increased country food consumption was strongly associated with higher PFAAs concentrations, particularly PFOS, PFDA, and PFUnDA. ...